2014
DOI: 10.3390/socsci3040606
|View full text |Cite
|
Sign up to set email alerts
|

“I Know People Think I’m a Complete Pain in the Neck”: An Examination of the Introduction of Child Protection and “Safeguarding” in English Sport from the Perspective of National Governing Body Safeguarding Lead Officers

Abstract: Child protection in sport emerged at the start of the 21st century amidst headlines about coaches raping, sexually assaulting and abusing children. Against this backdrop, in 2001 the UK government established an independent agency, the English Child Protection in Sport Unit (CPSU), which introduced national child protection standards for sports organizations. This included the requirement to appoint national "safeguarding lead officers". Utilizing the theoretical framework of sociologist Pierre Bourdieu, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The reluctance of sport organisations to implement child protection activities has been confirmed by other studies in this field (e.g. Donnelly and others, 2016;Hartill and Lang, 2014;Hartill and Prescott, 2007). Most studies focus on sport governing bodies (e.g.…”
Section: Child Protection In Sport Organisationsmentioning
confidence: 62%
“…The reluctance of sport organisations to implement child protection activities has been confirmed by other studies in this field (e.g. Donnelly and others, 2016;Hartill and Lang, 2014;Hartill and Prescott, 2007). Most studies focus on sport governing bodies (e.g.…”
Section: Child Protection In Sport Organisationsmentioning
confidence: 62%
“…While it is acknowledged that there are limitations to the CPSU’s approach (not least a lack of robust prevalence and incidence data and of research to evaluate the effectiveness of the CPSU’s strategy; see, for example, Hartill & Lang, 2014; Hartill & O’Gorman, 2015), blaming the CPSU and the introduction of safeguarding and child protection regulations for coaches’ concerns misrepresents the issue and fails to acknowledge the impact of wider societal discourses, organizational change, and the policy implementation process. For example, the current high media profile of sexual abuse in and beyond sport, which began in 2012 when claims surfaced against the recently deceased British TV presenter and charity fund-raiser Jimmy Savile, 2 has raised the profile of child abuse and particularly child sexual abuse—the Savile case, for example, has been credited with prompting a 9% rise in reports of sexual offenses across the country (Harmes, 2013).…”
Section: An Alternative Perspectivementioning
confidence: 99%
“…This is particularly the case when policies require significant change to established practice, and when those charged with implementation perceive that the policy introduces responsibilities they do not consider legitimate. This appears to be the case in sport; studies within sport have found that coaches are lacking in knowledge and confidence about safeguarding and child protection, and that some coaches and other sport stakeholders are reluctant to accept that children’s welfare is a legitimate part of their responsibility (Hartill & Lang, 2014; Pitchford, 2005), despite legislation that makes it clear that safeguarding is everyone’s responsibility, including those involved in sport (Department for Education and Skills, 2004).…”
Section: An Alternative Perspectivementioning
confidence: 99%
“…However, child protection and safeguarding has not been uniformly embraced. Indeed, critical perspectives have emerged from empirically and theoretically informed studies of sport (Brackenridge et al, 2007; Garratt et al, 2013; Hartill and Lang, 2014; Piper et al, 2013; Prescott and Hartill, 2007; Taylor et al, 2016). The critique raises concern about evoking ‘moral panic’ (Furedi, 2011) through excessive emphasis on risk and protection.…”
Section: Athlete Safety and Safeguarding In Sportmentioning
confidence: 99%